2015
DOI: 10.1097/won.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Teaching and Stoma Marking in an Inpatient Population

Abstract: Preoperative teaching and stoma marking are supported by research and included in clinical practice guidelines from the WOCN Society and others. Using a FOCUS-Plan-Do-Check-Act model of Total Quality Management, a multidisciplinary team was formed that developed a flow chart outlining the process of care for patients undergoing planned ostomy surgery that included an educational intervention that enabled staff nurses to perform preoperative stoma site marking and education. After 3 months, we found a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Observational studies published after 2015 showed a wide deviation from 12.1% to 86.2% for preoperative unmarked rates. Among the many barriers to hinder preoperative stoma site marking, the most well‐known and uncontrollable variable is the emergent nature of patient illness (Zimnicki, 2015). Emergency surgery makes it difficult for physicians and WOCNs to mark a surgical stoma site before surgery (Gok et al, 2019; Millan et al, 2010; Parmar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies published after 2015 showed a wide deviation from 12.1% to 86.2% for preoperative unmarked rates. Among the many barriers to hinder preoperative stoma site marking, the most well‐known and uncontrollable variable is the emergent nature of patient illness (Zimnicki, 2015). Emergency surgery makes it difficult for physicians and WOCNs to mark a surgical stoma site before surgery (Gok et al, 2019; Millan et al, 2010; Parmar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This project significantly increased the number of patients who had preoperative stoma site marking and education. 36 Stoma site marking is an important art and skill that is beyond the scope of this article to describe in detail. Major principles include observation of the patient's abdomen while standing, sitting, bending over, and lying down (Figure 1).…”
Section: Preoperative Care and Stoma Site Markingmentioning
confidence: 99%
“…Because specialized nurses may not be available 24/7, patients who undergo unplanned/emergency surgery may not benefit from preoperative education and stoma site marking. Accordingly, the literature supports the training of physicians and nonspecialty nurses to do stoma site marking 34–37 . Zimnicki 36 completed a quality improvement project to train nonspecialized nurses in stoma site marking.…”
Section: Preoperative Care and Stoma Site Markingmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDSA model in the first category is often used for small QI projects or changes, or rapid assessment of interventions, as well as for continuous feedback to overcome the resistances (37)(38)(39). This model is also more used to reduce waiting times.…”
mentioning
confidence: 99%